Desenho racional de fármacos sólidos com limitações farmacêuticas: cloridrato de raloxifeno e benzoilmetronidazol - Oliveira, Yara Santiago de (2019)
The use of supramolecular synthons as a strategy to control the crystal structure is the key to the development of new solid forms with physicochemical properties optimized by design. However, to achieve this objective, it is necessary to understand intermolecular interactions in the context of crystalline packing. Identifying potential hydrogen bonding sites in the Active Pharmaceutical Ingredient (API) and selecting the correct coformer, which has groups capable of performing complementary hydrogen bonds, is the initial step for the discovery of supramolecular synthons with pharmaceutical relevance. In this work the drugs raloxifene hydrochloride (RLC) and benzoylmetronidazole (BZMD) were used, due to their low solubility in water. RLC was screened by solvent selection. Concerning BZMD, the synthon imidazol ⋯ hydroxyl was investigated, and different stoichiometric IFA: coformer ratios were explored. The methods used to obtain new solid forms were mechanochemical activation, slow evaporation and cooling crystallization. Single-crystal X-ray diffraction was employed for structural elucidation, while characterization was performed by powder X-ray diffraction, vibrational spectroscopy and thermal analysis. The solubility was also performed, aiming to compare the profile of the new solid forms with the commercialized form. Related to RLC four clathrates were obtained with acetone, N, N-dimethylformamide, methanol and N,N-dimethylacetamide (guest solvents). In addition, a clathrate with N, N-dimethylformamide showed polymorphism (α and β polymorphs). The solubility of two of the novel structures exhibited improved dissolution rate in water when compared to the commercially available solid form. Related to BZMD, thirteen new solid forms (two salts and eleven cocrystals) were successfully produced, and the crystalline structures were elucidated, confirming the robustness of the selected synthon. The solubility of the salt with the conformer 2,6-dihydroxybenzoic acid (BZMD2,6DBA) showed the best solubility among the new solid forms analyzed, and the cocrystals with 3,5-dinitrobenzoic acid (BZMD3,5DNZ) and 4- methoxybenzoic acid (BZMDMAC) has a lower solubility than the other solid forms analyzed. Thus, this work successfully employed the rational design of structures, based on Crystal Engineering.